Strategi Pemasaran Yang Diterapkan Komunitas Sarilate Adventure Atau Sarilate Outdoor Equipment Untuk Meningkatkan Minat Konsumen Terhadap Produknya - Dwi Sri Tiara; Wafa Marwa Hanifah; Arifudin Arifudin (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Sarilate is a community that originated from the Al-Masyariqul Anwar Islamic boarding school in Babakan Village, Ciwaringin District, Cirebon Regency, West Java in 2015. The name Sarilate Adventure is Sarilate Adventure, which has an organizational structure including the chairman, deputy chairman, secretary, treasurer and public relations (public relations). In addition, there is another name for this community, namely Sarilate outdoor equipment, which means Sarilate outdoor equipment. Sarilate opens outdoor equipment rental and sells local products from Sarilate itself and also has product brands, namely Eiger and Balai. This business has carried out 3 stages of the marketing strategy, namely having targeted consumers, identifying consumer desires, and determining the marketing mix. In addition to the 3 stages of the marketing strategy, Sarilate also applies the concept of AIDA + S (Attention, Interest, Desire, Action, Satisfaction) which greatly influences increasing consumer interest in Sarilate products. This type of research is field research conducted with a qualitative approach. The methods used in collecting data for preparing this research report include observation, interviews and literature review. The purpose of this research is to find out the marketing strategy applied by Sarilate Adventure or Sarilate Outdoor Equipment to increase consumer interest in their products.